1994
DOI: 10.1172/jci117395
|View full text |Cite
|
Sign up to set email alerts
|

Antimyenteric neuronal antibodies in scleroderma.

Abstract: The pathogenesis of gastrointestinal (GI) dysmotility in scleroderma is incompletely understood, although previous studies have proposed a neuropathic mechanism. We studied patients with scleroderma as compared with other connective tissue disease patients and normal controls for the presence of circulating antibodies to myenteric neurons. Serial dilutions of sera were overlaid on rat intestine, doublelabeled with antineurofilament antibody as a myenteric plexus marker, and imaged using indirect immunofluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(38 citation statements)
references
References 27 publications
1
35
0
2
Order By: Relevance
“…2). Howe et al identified autoantibodies to enteric neurons in 15 of 41 patients, suggesting a possible immune-mediated dysfunction of enteric neurons [14]. Antibodies against the muscarinic M3 receptor have been identified in a small group of patients with scleroderma and severe gastrointestinal complications.…”
Section: Pathogenesismentioning
confidence: 99%
“…2). Howe et al identified autoantibodies to enteric neurons in 15 of 41 patients, suggesting a possible immune-mediated dysfunction of enteric neurons [14]. Antibodies against the muscarinic M3 receptor have been identified in a small group of patients with scleroderma and severe gastrointestinal complications.…”
Section: Pathogenesismentioning
confidence: 99%
“…A recent study has found a high incidence of antimyenteric neuronal antibodies in the sera of SSc patients with GI symptoms (22). A follow-up study showed that passive transfer of these antibodies into a rat model significantly disrupts intestinal myoelectric activity (15), further supporting a neuropathic etiology to dysmotility in SSc patients.…”
mentioning
confidence: 95%
“…However, 19 of 25 patients without anti-myenteric antibodies also had GI dysfunction, casting doubt on a direct causative role (Howe et al 1994). IgG against mAChRs were detected by radioimmunoprecipitation in 7 of 9 scleroderma patients with gastrointestinal symptoms.…”
Section: Specificity For Diseasementioning
confidence: 98%
“…The sera of scleroderma patients has also been found to contain antibodies capable, in immunofluorescent assays, of binding myenteric neurons (Howe et al 1994). Anti-muscarinic AChR (mAChR) autoantibodies have also been identified in patients with SSc and GI dysfunction (see below for further discussion) (Goldblatt et al 2002;Kawaguchi et al 2009).…”
Section: Detection Of Autoantibodiesmentioning
confidence: 99%